1996
DOI: 10.1152/jappl.1996.81.5.1996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cigarette smoke extract on arteriolar dilatation in vivo

Abstract: The goal of this study was to determine whether cigarette smoke extract alters dilatation of arterioles in vivo in response to agonists that produce activation of ATP-sensitive potassium channels and activation of adenylate cyclase. By using intravital microscopy, we measured diameter of arterioles contained within the microcirculation of the hamster cheek pouch during suffusion with agonists in the absence and presence of cigarette smoke extract (0.1, 0.5, and 1.0%). Before treatment with cigarette smoke extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 49 publications
2
16
0
2
Order By: Relevance
“…It is therefore considered to be atheroprotective. Both active and passive smokers show decreased vasodilatation [52][53][54] , which corroborates many studies that have shown that cigarette smoke is associated with decreased NO availability 54,69 . Several studies investigated the molecular pathways leading to decreased NO availability in smokers.…”
Section: Effect Of Cigarette Smoking On the Endotheliumsupporting
confidence: 83%
See 1 more Smart Citation
“…It is therefore considered to be atheroprotective. Both active and passive smokers show decreased vasodilatation [52][53][54] , which corroborates many studies that have shown that cigarette smoke is associated with decreased NO availability 54,69 . Several studies investigated the molecular pathways leading to decreased NO availability in smokers.…”
Section: Effect Of Cigarette Smoking On the Endotheliumsupporting
confidence: 83%
“…In the case of atherosclerosis, it has been demonstrated that intimal-medial thickness, a routine measurement to determine the advancement of atherosclerosis, is increased in both passive and active smokers 51 . Furthermore, both active and passive smoking are associated with decreased vasodilatation in various vascular beds (in different sites in the arteries) 52,53,54 . Finally, cigarette smoking significantly increases, LDL levels 55 , lipid oxidation, leukocyte counts and inflammatory markers in humans 56,57,58 (see section I.3.b), all of these processes being known to favor plaque growth.…”
Section: I3a the Pathophysiology Linking Smoking And Atherosclerosismentioning
confidence: 99%
“…Nicotine can contribute to the development of cardiovascular disorders through a variety of mechanisms. It has been shown that the most significant effects of nicotine are through its influence on the vascular tone (Mayhan and Sharpe, 1996;Wang and Wang, 2000), the hemostatic system (Powell, 1998), and the endothelium (Mayhan et al, 1999). The combination of these effects leads to the development of various cardiovascular disorders such as atherosclerosis, cardiac arrhythmias, coronary artery disease, and hypertension.…”
mentioning
confidence: 99%
“…Several studies have reported that cigarette smoking exposes individual to cardiovascular morbidity and mortality (Mayhan and Sharpe, 1996). Troponin I is considered as valuable biomarker to convey prognostic information for patient with non ST-elevation myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking is one of the most important risk factors for acute coronary syndrome. Smoking impacts all the phases of atherosclerosis (Mayhan and Sharpe, 1996). In Bangladesh over 50% male and 3% female are cigarette smokers (Millat, 2005).…”
Section: Introductionmentioning
confidence: 99%